The timing and magnitude of Stroop interference and facilitation in monolinguals and bilinguals - Coderre, Emily L.; van Heuven, Walter J.B.; Conklin, Kathy (Cambridge University Press, 2013)
Executive control abilities and lexical access speed in Stroop performance were investigated in English monolinguals and two groups of bilinguals (English–Chinese and Chinese–English) in their first (L1) and second (L2) languages. Predictions were based on a bilingual cognitive advantage hypothesis, implicating cognitive control ability as the critical factor determining Stroop interference; and two bilingual lexical disadvantage hypotheses, focusing on lexical access speed. Importantly, each hypothesis predicts different response patterns in a Stroop task manipulating stimulus onset asynchrony (SOA). There was evidence for a bilingual cognitive advantage, although this effect was sensitive to a number of variables including proficiency, language immersion, and script. In lexical access speed, no differences occurred between monolinguals and bilinguals in their native languages, but there was evidence for a delay in L2 processing speed relative to the L1. Overall, the data highlight the multitude of factors affecting executive control and lexical access speed in bilinguals.